Research progress of dynamic community evolution - Jianfei PAN; Lili XU; Yihong DONG (Dianxin kexue)
Community structure is one of the topological characteristics of social network.It is an important research topic in social network research to explore the structure of community,detect and predict the change of community structure.The evolution of dynamic community was discussed from time slicing processing and dynamic increment strategies.The time slice processing strategy introduced the comparative evolution of the time slice,the clustering evolution of the time slice,and the fusion evolution of the time slice.The dynamic increment strategy described the dynamic evolution of the core community,the dynamic evolution of the cluster and the dynamic evolution of the index.Finally,the framework of community evolution prediction was summarized.